Analisis Kekuatan Lentur Pegas Daun Truk dan Mobil Hasil Tempering - Raihan Insan Nararya; Kris Witono; Asrori Asrori; Eko Yudiyanto; Syamsul Hadi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Leaf springs are one of the suspension systems that are still widely used in various modes of transport such as cars and trucks. The spring functions to support the load and reduce vibration from operational activities. This study aims to analyse the bending strength and hardness of steel leaf springs of trucks and cars resulting from tempering heat treatment. The three point bending method was used as the flexural strength testing method and the Rockwell C Hardness method testing was used for hardness testing with leaf springs in raw, tempered 460°C, and tempered 510°C conditions. From the results of the study, the highest average bending strength value of 3733,55 MPa was obtained and an average roughness value of 31,8 HR was obtained for the 510°C tempered truck leaf springs. This also applies to the 510°C tempered car leaf springs, where the average bending strength value obtained is 3392,65 MPa and the average hardness value obtained is 29,5 HR. Thus, it is recommended that tempering heat treatment that can be applied to truck and car leaf springs be carried out at 510°C to increase the bending strength and ductility of the leaf springs.